Wer bleibt nach einer Famulatur in Orthopädie und Unfallchirurgie dem Fachbereich treu?: Ergebnisse einer bundesweiten Umfrage = Who stays loyal to orthopaedics and trauma surgery? : results of a nationwide survey - Kasch, Richard; Wirkner, Janine; Meder, Adrian; Abert, E.; Abert, M.; Schulz, Arndt-Peter; Walcher, Felix; Gümbel, Denis Dominic; Obertacke, Udo; Schwanitz, P.; Merk, Harry Rudolf; Fröhlich, Susanne (Zeitschrift für Orthopädie und Unfallchirurgie, 2016)
Introduction: The general shortage of medical doctors in Germany can also be felt in the area of trauma and orthopaedics. Medical elective placements, in Germany known as “Famulatur”, are sensitive interfaces between the theoretical university studies and the practical medical workplace. In this research project, the aim was to study how medical students perceive these types of placements and if it alters their decision making when planning their further career. Methods: During the summer term of 2012, 9079 medical students answered an online questionnaire. Of these, the subgroup was evaluated that had had a placement of at least 4 weeks in the field of trauma and orthopaedics. Overall, 37 test items about this placement and further career steps were included in this study. Groups were evaluated separately by the item “I am considering a career in trauma and orthopaedics” (PJ-Ja) versus “I am not considering a career in trauma and orthopaedics” (PJ-Nein). Results: Overall 397 students were included in this study; 55% were female. 267 (67.3%) stated: “I am considering a career in trauma and orthopaedics”; 130 (32.7%) were not. There was no significant difference in age or sex between these groups (sex: χ²= 2.50, p = 0.114; age: F[1.93]< 1, p = 0.764). Specific and statistically significant differences between those groups were found in the items team integration, ward climate, qualification of teaching, training for specific knowledge in the field, practical aspects of the tasks performed, general planning and structure of the elective achievement of the teaching goals. Discussion: Knowledge of satisfaction during medical elective placements is essential if one aims to inspire students for a specific medical profession. Instructors who can identify weaknesses and deficits in their training regime can therefore in the future increase the number of medical doctors who choose their speciality. The foundation of personal development has to be laid very early in the career of medical students.
Gesehen am 08.08.2019